2009
DOI: 10.1530/rep-09-0152
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and conceptus elongation in cattle: a direct effect on the embryo or an indirect effect via the endometrium?

Abstract: The steroid hormone progesterone (P 4 ) plays a key role in the reproductive events associated with pregnancy establishment and maintenance. High concentrations of circulating P 4 in the immediate post-conception period have been associated with an advancement of conceptus elongation, an associated increase in interferon-t production and higher pregnancy rates in cattle. Using in vitro and in vivo models and w8500 bovine oocytes across six experiments, the aim of this study was to establish the route through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
230
3
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 294 publications
(261 citation statements)
references
References 39 publications
16
230
3
12
Order By: Relevance
“…Nevertheless, embryos that were transferred into recipients that had received prior P4 exposure (days 3 to 6 increased P4) had longer embryos on day 14 and embryo area was much greater (Clemente et al, 2009). The authors concluded that 'P4-induced changes in the uterine environment are responsible for the advancement in conceptus elongation reported previously in cattle and that, interestingly, the embryo does not need to be present during the period of high P4 in order to exhibit advanced elongation ' (Clemente et al, 2009). These results are consistent with the studies of (Larson et al, 2011) that also failed to find a direct effect of P4 during either days 1 to 3 or days 4 to 7 of culture on percentage of embryos that developed to the morula or blastocyst stage; although small differences in glucose metabolism were observed.…”
Section: Importance Of High P4 After Aimentioning
confidence: 98%
See 4 more Smart Citations
“…Nevertheless, embryos that were transferred into recipients that had received prior P4 exposure (days 3 to 6 increased P4) had longer embryos on day 14 and embryo area was much greater (Clemente et al, 2009). The authors concluded that 'P4-induced changes in the uterine environment are responsible for the advancement in conceptus elongation reported previously in cattle and that, interestingly, the embryo does not need to be present during the period of high P4 in order to exhibit advanced elongation ' (Clemente et al, 2009). These results are consistent with the studies of (Larson et al, 2011) that also failed to find a direct effect of P4 during either days 1 to 3 or days 4 to 7 of culture on percentage of embryos that developed to the morula or blastocyst stage; although small differences in glucose metabolism were observed.…”
Section: Importance Of High P4 After Aimentioning
confidence: 98%
“…An elegant series of experiments found no effect of P4 supplementation after fertilization, in vitro, on blastocyst yield, in the presence or absence of bovine oviductal epithelial cells (Clemente et al, 2009). In a surprising twist, these researchers treated recipient cows with an intravaginal P4-releasing device (PRID) starting on day 3 after estrus with in vitro produced blastocysts transferred on day 7.…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
See 3 more Smart Citations